Development and validation of a spectrofluorimetric method for the estimation of camptothecin in bulk and formulation - Bhusari, Sachin Shivling; Chaudhari, Tejal Prashant; Wakte, Pravin Shridhar (Journal of Drug Delivery and Therapeutics, 2019)
A simple, accurate, precise, sensitive and cost-effective spectrofluorimetric method was developed and validated for the estimation of Camptothecin (CMPTO) in bulk and formulation. The relative fluorescence intensity of Camptothecin was measured in distilled water at an excitation wavelength of 278 nm and an emission wavelength of 419 nm. Proposed method was found to be linear over the range of 50 to 3000 ng/ml with correlation coefficient 0.9999. Proposed method was validated using different analytical method validation parameters viz. accuracy, precision, LOD, LOQ, robustness and ruggedness using QC standards as per the ICH guidelines. Thepercentage recovery was found to be 100.64 % and percentage RSD values were found to be less than 2 for accuracy and precision studies. The detection and quantification limits for the proposed method were found to be 15.76 and 47.98 ng/ml, respectively. A simple, accurate, precise, sensitive yet cost-effective spectrofluorimetric method was developed for the estimation of CMPTO in bulk and formulation. The said spectrofluorimetric method was found to be economic as it comprises water as a solvent.Keywords: Spectrofluorimetry, Camptothecin, Validation, Excitation, Emission